Fabric‐Assisted MXene/Silicone Nanocomposite‐Based Triboelectric Nanogenerators for Self‐Powered Sensors and Wearable Electronics. (17th October 2021) - Salauddin, Md; Rana, S. M. Sohel; Rahman, Muhammad Toyabur; Sharifuzzaman, Md.; Maharjan, Pukar; Bhatta, Trilochan; Cho, Hyunok; Lee, Sang Hyun; Park, Chani; Shrestha, Kumar; Sharma, Sudeep; Park, Jae Yeong
Abstract: Surface modification of triboelectric negative layers is an essential factor for boosting the output performance of triboelectric nanogenerators (TENGs). Herein, a novel scalable surface modification method is introduced using a fabric‐assisted micropatterning technique on a highly negative MXene/silicone nanocomposite surface (charge generating) with MXene layer (charge trapping) for self‐powered sensors and wearable electronics. The microstructured surface is fabricated directly from a fabric template requiring no surface‐active agent, high‐pressure equipment, or high vacuum. To boost the proposed double‐side‐contact TENG (DSC‐TENG) output performance, different parameters of the fabric textures are tested and optimized for the roughened microstructures, namely the MXene layer and relative humidity. Under optimal conditions, the fabricated DSC‐TENG improves the voltage and peak current density by factors of 9.8 and 20, respectively, regarding flat silicone. It exhibits a maximum peak power density of 55.47 W m −2 at load resistance of 0.18 MΩ, and a corresponding decrease in resistance by 75% using MXene content of 3 mg cm −2 . Also, DSC‐TENG‐based smart home control of electrical appliances, theft protection, self‐powered electronic devices, password authentication, and human motion monitoring via smartphone for the IoT are demonstrated. The proposed method can be implemented for different types of polymers, thereby enabling the large‐scale fabrication of high‐performance TENGs in industrial applications. Abstract : A fabric electrode and double‐side‐contact TENG (DSC‐TENG) based on a fabric‐assisted micropatterning method on a highly negative MXene/silicone nanocomposite surface (charge generating) with MXene layer (charge trapping) for self‐powered sensors and wearable electronics applications. The intentionally designed DSC‐TENG is waterproof, safe from humidity, and exhibits stable and durable output performance, soft, and comfortable wearing.